2014
DOI: 10.1177/0960327114561343
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C-η in cigarette smoke extract-induced apoptosis in MRC-5-cells

Abstract: Cigarette smoke (CS) is a major risk factor for emphysema, which causes cell death in structural cells of the lung by mechanisms that are still not completely understood. We demonstrated previously that CS extract (CSE) induces caspase activation in MRC-5 human lung fibroblasts, activated protein kinase C-η (PKC-η), and translocated PKC-η from the cytosol to the membrane. The objective of this study was to investigate the involvement of PKC-η activation in a CSE-induced extrinsic apoptotic pathway. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…22) Activation and translocation of PKCη to the plasma membrane are essential for CSE-induced apoptosis via upregulation of caspase 3 and 8 in human lung fibroblasts (MRC-5 cells). 23) In addition, CSE-induced apoptosis of MRC-5 cells is inhibited by PKCα but promoted by PKCζ. 24) PKCε activation in response to coexposure to cigarette smoke and alcohol decreases airway epithelial cell cilia beating.…”
Section: Involvement Of Protein Kinase C-depen-dent Activation Of Nadmentioning
confidence: 99%
“…22) Activation and translocation of PKCη to the plasma membrane are essential for CSE-induced apoptosis via upregulation of caspase 3 and 8 in human lung fibroblasts (MRC-5 cells). 23) In addition, CSE-induced apoptosis of MRC-5 cells is inhibited by PKCα but promoted by PKCζ. 24) PKCε activation in response to coexposure to cigarette smoke and alcohol decreases airway epithelial cell cilia beating.…”
Section: Involvement Of Protein Kinase C-depen-dent Activation Of Nadmentioning
confidence: 99%
“…Other research has shown that exposure to CSE increases inflammation, 5 and inhibits the proliferation and migration in healthy lung fibroblasts 8 CSE has also been shown to induce senescence, increase collagen production, and increase apoptosis and necrosis (at CSE concentrations above 40%) in healthy lung fibroblasts. [9][10][11][12] Although these studies only investigated a narrow range of variables, CSE clearly affects healthy (or cell line) lung fibroblast cells; however, the effects of CSE on lung fibroblasts from COPD subjects are still poorly understood. A concerning note is that many studies assume that healthy lung fibroblasts will respond to CSE the same way as COPD lung fibroblasts that may present false-positive biomarkers of interest for COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Like other kinases, CK1α performs multiple biological processes such as cell division, cell cycle, beta-catenin destruction and cell morphogenesis, signal transduction, WNT signaling pathway, etc. [8][9][10][11][12][13][14]. Pharmacological inhibition of CK1α has been investigated as a potential therapy in various diseases, including cancers [15].…”
Section: Introductionmentioning
confidence: 99%